Pengembangan LKPD Elektronik IPA dengan Model Problem-Based Learning (PBL) untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Kelas VII di SMP Muhammadiyah 1 Palembang: (Developing Electronic Science Student Worksheets Using the Problem-Based Learning (PBL) Model to Improve Critical Thinking Skills in Grade VII Students at Muhammadiyah 1 Junior High School, Palembang) - Ikopala, Silvyanda; Hidayat, Saleh; Syahri, Indawan (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
The purpose of this study was to determine: 1) the validity of the E-LKPD (Electronic Student Worksheet) IPA (Natural Sciences) product developed with the PBL (Problem Based-Learning) model according to material experts, language experts, media experts, teaching materials experts, evaluation experts and learning device experts, 2) the practicality of the E-LKPD IPA product developed with the PBL model based on teacher and student responses, 3) the effectiveness of the E-LKPD IPA product that will be developed with the PBL model to improve critical thinking skills of grade VII students. The development model used is the 4D model by Thiagarajan., et al. (1974) namely define, design, develop, and disseminate. The resulting product is an E-LKPD regarding the classification of living things for grade VII students that is valid, practical, and effective. The validity of the E-LKPD with the PBL model that has been carried out by the validator gets valid and very valid qualification results. Practicality was obtained from the results of the E-LKPD readability questionnaire trial showing a strong response. E-LKPD using the PBL model on the material of classification of living things was proven to be more effective in improving students' critical thinking skills compared to the control class that did not receive E-LKPD treatment. The effectiveness value can be measured through the N-Gain results with experimental classes 1 and 2 achieving a value of 0.7 which is included in the high category while control class 1 obtained a value of 0.3 which is included in the low category and control class 2 obtained a value of 0.6 which is included in the medium category Abstrak. Tujuan penelitian ini adalah untuk mengetahui: 1) kevalidan produk E-LKPD IPA yang dikembangkan dengan model PBL menurut ahli materi, ahli bahasa, ahli media, ahli bahan ajar, ahli evaluasi dan ahli perangkat pembelajaran, 2) kepraktisan produk E-LKPD IPA yang dikembangkan dengan model PBL berdasarkan respon guru dan peserta didik, 3) keefektifan produk E-LKPD IPA yang akan dikembangkan dengan model PBL untuk meningkatkan keterampilan berpikir kritis peserta didik kelas VII. Model pengembangan yang digunakan yaitu model 4D oleh Thiagarajan., et al. (1974) yaitu define, design, develop, dan disseminate. Produk yang dihasilkan adalah E-LKPD mengenai klasifikasi makhluk hidup untuk peserta didik kelas VII yang valid, praktis, dan efektif. Kevalidan E-LKPD dengan model PBL yang telah dilakukan oleh validator mendapatkan hasil kualifikasi valid dan sangat valid. Kepraktisan diperoleh dari hasil uji coba angket keterbacaan E-LKPD menunjukkan respon kuat. E-LKPD yang menggunakan model PBL pada materi klasifikasi makhluk hidup terbukti lebih efektif dalam meningkatkan keterampilan berpikir kritis peserta didik dibandingkan dengan kelas kontrol yang tidak mendapatkan perlakuan E-LKPD. Nilai keefektifan dapat diukur melalui hasil N-Gain dengan kelas eksperimen 1 dan 2 mencapai nilai 0,7 yang termasuk dalam kategori tinggi sedangkan kelas kontrol 1 memperoleh nilai 0,3 yang termasuk dalam kategori rendah dan kelas kontrol 2 memperoleh nilai 0,6 yang termasuk ke dalam kategori sedang.